2012
DOI: 10.5336/medsci.2011-24291
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Stapler Size Used in Esophagojejunostomy Anastomosis: Anastomotic Leak and Strictures After Total Gastrectomy

Abstract: diameters and strictures following esophagectomy and total gastrectomy in 256 patients. World J Surg 2000;24(1):78-84.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…Twenty-one studies were included (Table 1), representing a total of 7226 patients [12,13,15,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Seven oesophageal, twelve gastric, and three lower GI studies were identified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-one studies were included (Table 1), representing a total of 7226 patients [12,13,15,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Seven oesophageal, twelve gastric, and three lower GI studies were identified.…”
Section: Resultsmentioning
confidence: 99%
“…The seven oesophageal studies encompassed 1081 patients [13,27,28,32,[35][36][37]. For the pooled oesophageal anastomosis studies, a clear increase in stricture rates was observed with the use of smaller circular stapler diameters.…”
Section: Oesophageal Anastomosismentioning
confidence: 99%
“…22 In this meta-analysis, 5 observational studies were included. [23][24][25][26][27][28] It was concluded that the use of larger circular stapler size (28 mm versus 25 mm) was strongly associated with a reduced risk of postoperative anastomotic strictures in the upper GI tract. 22 Results from our study do not support the conclusion of aforementioned meta-analysis, as there were no differences observed in anastomotic insufficiency and postoperative anastomotic strictures between the 25 mm and the 28 mm stapled esophagogastric anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…When trying to decrease anastomotic leak rates for instance, Çakabay et al emphasized the importance of meticulous technique and suggested a protocol-driven approach. 35 Additional studies also support the concept that a surgeon’s experience with a given device is a key determinant in patient outcomes. A review of operative reports and web-based charts for colon and rectal resections at Brigham and Women’s Hospital (Boston) found that 19% of these procedures featured a technical error involving the stapling device.…”
Section: A Framework For the Study Of Device Tissue And Their Intermentioning
confidence: 90%
“…When trying to decrease anastomotic leak rates for instance, Çakabay et al emphasized the importance of meticulous technique and suggested a protocol-driven approach 35. Additional studies also support the concept that a surgeon’s experience with a given device is a key determinant in patient outcomes.…”
Section: A Framework For the Study Of Device Tissue And Their Intermentioning
confidence: 99%